PROCESS OF PROVISION OF ADMINISTRATIVE SERVICES IN ELECTRONIC FORM IN LOCAL AUTHORITIES: RESEARCH RESULTS OF 2016 - Serenok A.O. (Pressing Problems of Public Administration, 2017)
The results of monitoring e-governance tools of local authorities in largest cities of Ukraine have been analyzed to assessment of informational fullness of of cial web-sites of local authorities and process of provision of administrative services in electronic form.